Graphene materials based on benzoxazine compounds and preparation methods and applications thereof
By using a method combining benzoxazine compounds with laser technology, they are directly converted into graphene materials, which solves the problem of low efficiency of precursor material attachment and functional modification in the existing technology, and realizes low-cost and efficient graphene. Material preparation.
Patent Information
- Application Number
- CN202211385959.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-11-07
AI Technical Summary
In the prior art, the precursor material of laser-induced graphene material has the problem of being closely attached to the substrate surface during preparation and application, which is difficult to detach, and has low functional modification efficiency and is time-consuming and energy-consuming.
The phenylzide compound is used as the front -wheel drive, which is directly converted into graphene materials through laser irrades, simplifies the process process, reduces energy consumption, and achieves efficient modifications through uniform mixing with doping agents.
The low cost, efficient, and flexible preparation of graphene materials has been realized, and the problem of attachment and functional modification efficiency of the front -drive body material is solved, and it is suitable for large -scale industrialized production.
Smart Images

Figure CN115924894B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material technology, and specifically relates to a graphene material based on benzoxazine compounds and a preparation method and application thereof. Background Art
[0002] Laser-induced graphitization refers to the technology of converting carbon-containing precursor materials into graphene materials by laser ablation. The obtained graphene materials are usually called laser-induced graphene (LIG), which usually contain three components: few-layer graphene, graphite and amorphous carbon. Under the irradiation of laser, the molecular bonds of the precursor material undergo breaking and reorganization, most of which are reorganized into gas products and released quickly, while the carbon element is partially reorganized into graphite materials, and finally forms a porous honeycomb LIG. Compared with other methods for preparing graphene materials, this method of using laser one-step generation has attracted widespread attention from researchers around the world due to its advantages such as short preparation cycle, low cost, and applicability to roll-to-roll generation. After years of development, the precursor materials used to prepare LIG have been greatly expanded and can be mainly divided into two categories: synthetic polymers and natural polymers. The former includes high-performance thermosetting polymers such as polyimide, polyethersulfone, and polybenzoxazine, while the latter is represented by natural bamboo and wood materials. Natural polymers are often less used because of their complex composition and poor reproducibility of product performance.
[0003] However, whether synthetic polymers or natural polymer materials are used as precursors for preparing LIG, there are two key defects in practical applications: 1) Since polymer materials are infusible and insoluble, the generated LIG is tightly attached to the surface of the precursor material and is difficult to detach, which greatly limits the application scenarios, such as Nature communications, 2014, 5, 5714., ACS nano, 2018, 12, 2176-2183. and patent CN110482531A; 2) When functionally modifying the precursor components, it can only be done through chemical grafting, vacuum impregnation or co-curing, which is time-consuming and energy-consuming and has low doping efficiency, such as ACS Appl. Nano Mater. 2018, 1, 5053-5061, patent CN113060721A, patent CN113549207A. How to overcome the shortcomings of the current existing technology and achieve low-cost, efficient and flexible preparation is of great practical significance for the further development and application of this type of laser-induced graphene materials. Summary of the invention
[0004] The main purpose of the present invention is to provide a graphene material based on benzoxazine compounds and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] An embodiment of the present invention provides a method for preparing a graphene material based on benzoxazine compounds, which comprises: irradiating the benzoxazine compounds with a laser to convert the benzoxazine compounds into a graphene material based on benzoxazine compounds;
[0007] Wherein, the benzoxazine compound includes a benzoxazine monomer and / or a benzoxazine monomer derivative; and the benzoxazine compound is a liquid material.
[0008] The embodiment of the present invention also provides a graphene material based on benzoxazine compounds prepared by the aforementioned preparation method.
[0009] The embodiment of the present invention further provides a method for preparing a graphene hybrid material and / or a graphene composite material based on benzoxazine compounds, which comprises:
[0010] The aforementioned benzoxazine compound is mixed with a doping precursor to form a composition, and then the composition is irradiated with a laser to obtain a graphene hybrid material and / or a graphene composite material based on the benzoxazine compound.
[0011] The embodiments of the present invention also provide a graphene hybrid material and / or a graphene composite material based on benzoxazine compounds prepared by the aforementioned preparation method.
[0012] The embodiments of the present invention also provide applications of the aforementioned graphene material or graphene hybrid material and / or graphene composite material in the fields of energy storage, energy conversion, catalysis, sensing or electromagnetic shielding.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] (1) The precursor used to prepare the graphene material (LIG material) in the present invention is a benzoxazine monomer and / or a benzoxazine monomer derivative, which does not require a further high-temperature curing process and a complicated molding process. That is, the benzoxazine monomer and / or the benzoxazine monomer derivative can be directly converted into a graphene material by laser irradiation. Therefore, the entire implementation process is more concise and energy-saving, and the operation is simple, easy to implement, low-cost and suitable for large-scale industrial production;
[0015] (2) The benzoxazine monomer and / or benzoxazine monomer derivative used in the present invention is fusible and soluble, and the unconverted monomer can be removed by solvent to allow LIG to exist in a substrate-free form and be further utilized, or the benzoxazine monomer can be coated on a target substrate material and then laser irradiated to generate a corresponding LIG functional coating in one step. This flexibility in designing the form of LIG further expands the application scope of LIG and has broad development and application prospects;
[0016] (3) The benzoxazine monomer and / or benzoxazine monomer derivative provided by the present invention can be directly and evenly mixed with the dopant in a molten state (liquid state), and compared with traditional precursor modification methods such as impregnation, chemical grafting, and co-curing, it can be compatible with more types of dopants and corresponding doping amounts. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 is the NMR spectrum of the benzoxazine monomer in Example 1 of the present invention;
[0019] Figure 2 This is a demonstration diagram of generating graphene material by laser irradiation of benzoxazine monomer in Example 1 of the present invention;
[0020] Figure 3 is a digital photograph of the patterned graphene material on the surface of the PET film prepared in Example 1 of the present invention;
[0021] Figure 4 is a scanning electron microscope image of the graphene material prepared in Example 1 of the present invention;
[0022] Figure 5 is the Raman spectrum of the graphene material prepared in Example 1 of the present invention;
[0023] Figure 6 is a transmission electron microscope image of the graphene material prepared in Example 1 of the present invention;
[0024] Figure 7 is a digital photograph of the patterned graphene material on the surface of the cotton cloth prepared in Example 2 of the present invention;
[0025] Figure 8is a digital photograph of the independent self-supporting graphene material film prepared in Example 3 of the present invention;
[0026] Figure 9a-9c The scanning electron microscope image, Raman spectrum data graph and X-ray photoelectron spectrum data graph of the nitrogen-doped graphene hybrid material prepared in Example 8 of the present invention;
[0027] Fig.10 The TiO prepared in Example 9 of the present invention 2 X-ray diffraction images of TiC nanoparticles and graphene composites loaded with TiC nanoparticles. DETAILED DESCRIPTION
[0028] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a graphene material based on benzoxazine compounds involves: irradiating a benzoxazine compound with a laser to convert the benzoxazine compound into a graphene material based on a benzoxazine compound;
[0030] Wherein, the benzoxazine compounds include benzoxazine monomers and / or benzoxazine monomer derivatives.
[0031] Furthermore, the benzoxazine compound is a fusible and soluble non-polymeric molecule.
[0032] Furthermore, the benzoxazine compound is a benzoxazine compound with high carbon-forming property.
[0033] In some preferred embodiments, the wavelength of the laser is 10.6 μm to 248 nm.
[0034] In some preferred embodiments, the graphene material comprises few-layer graphene.
[0035] Furthermore, the number of layers of the graphene material is 2 to 9.
[0036] Furthermore, the graphene material also includes a small amount of graphite and / or amorphous carbon.
[0037] In some preferred embodiments, the preparation method comprises: reacting a mixed reaction system comprising a phenol source, an amine source, polyformaldehyde and / or formaldehyde at 70 to 120° C. for 4 to 8 hours to obtain the benzoxazine monomer.
[0038] Further, the phenol source has a structure as shown in formula (I):
[0039]
[0040] Among them, R 1 , R 2 , R 3 , R 4 Each is independently selected from any one of a hydrogen atom, a hydroxyl group, a carboxyl group, a nitro group, a halogen group, a substituted or unsubstituted alkyl group, an olefin group, an ester group, an alkoxy group, a phenyl group, and a naphthyl group.
[0041] Furthermore, the amine source has a structure as shown in formula (II):
[0042] H 2 NR 5
[0043] Formula (II)
[0044] Among them, R 5 is selected from substituted or unsubstituted phenyl, furfuryl or naphthyl.
[0045] Furthermore, the functional group molar ratio of the phenol source, the amine source and the polyoxymethylene and / or formaldehyde is 1:0.5-2:1-5.
[0046] In some preferred embodiments, the preparation method comprises: reacting the benzoxazine monomer with any one of an acyl halide, an alcohol or an alkyl halide to obtain the benzoxazine monomer derivative.
[0047] Furthermore, the acyl halide has a structure as shown in formula (III):
[0048]
[0049] Wherein, X is selected from chlorine, bromine or iodine, R 6 is selected from substituted or unsubstituted alkyl, alkoxy, phenyl or naphthyl.
[0050] Furthermore, the alcohol or alkyl halide has a structure as shown in formula (IV):
[0051] XR 7
[0052] Formula (IV)
[0053] wherein X is selected from hydroxyl, chlorine, bromine or iodine, R 7is selected from substituted or unsubstituted alkyl, alkoxy, phenyl or naphthyl.
[0054] In some more specific embodiments, the preparation method of the graphene material based on benzoxazine compounds (referred to as: LIG material) includes: using a phenol source, an amine source, polyformaldehyde or formaldehyde and a solvent as raw materials to synthesize a benzoxazine monomer through a Mannich reaction, and then converting it into a graphene material through laser irradiation.
[0055] In some more specific embodiments, the preparation method of the graphene material based on benzoxazine compounds includes: using a phenol source, an amine source, polyformaldehyde or formaldehyde and a solvent as raw materials to synthesize a benzoxazine monomer; then grafting a target functional group onto the molecular structure of the benzoxazine monomer by a chemical grafting method to obtain a benzoxazine monomer derivative; and finally converting the obtained benzoxazine monomer derivative into a LIG material by laser irradiation.
[0056] Another aspect of the embodiments of the present invention further provides a graphene material based on benzoxazine compounds prepared by the aforementioned preparation method.
[0057] Another aspect of the embodiments of the present invention further provides a method for preparing a graphene hybrid material (denoted as: LIG hybrid material) and / or a graphene composite material (denoted as: LIG composite material) based on benzoxazine compounds, comprising:
[0058] The aforementioned benzoxazine compound is mixed with a doping precursor to form a composition, and then the composition is irradiated with a laser to obtain a graphene hybrid material and / or a graphene composite material based on the benzoxazine compound.
[0059] In some preferred embodiments, the doping precursor is a liquid and / or powder containing any organic and / or inorganic substances.
[0060] Furthermore, the doping precursor includes any one or a combination of two or more of metal nanoparticles, metal oxide nanoparticles, metal carbide nanoparticles, metal salts, metal organic compounds, MXene, graphene and its derivatives, carbon nanotubes, carbon fibers, carbon nanofibers, zeolites, nitrides, boric acid, borate esters, phosphides, sulfides, and fluorides, and is not limited thereto.
[0061] In some more specific embodiments, the method for preparing the graphene hybrid material based on benzoxazine compounds includes: mixing the aforementioned benzoxazine compounds with a liquid and / or powder of an organic matter containing at least one element of N, P, S, B, and F to form a composition, and then irradiating the composition with a laser to obtain the graphene hybrid material based on benzoxazine compounds.
[0062] In some more specific embodiments, the method for preparing the graphene composite material based on benzoxazine compounds includes: mixing the aforementioned benzoxazine compounds with liquid and / or powder of inorganic and / or metal organic compounds to form a composition, and then irradiating the composition with a laser to obtain the graphene composite material based on benzoxazine compounds.
[0063] In some preferred embodiments, the wavelength of the laser is 10.6 μm to 248 nm.
[0064] In some preferred embodiments, the graphene hybrid material and / or graphene composite material includes few-layer graphene.
[0065] Furthermore, the graphene hybrid material and / or graphene composite material also includes a small amount of graphite and / or amorphous carbon.
[0066] Another aspect of the embodiments of the present invention further provides a graphene hybrid material and / or a graphene composite material based on benzoxazine compounds prepared by the aforementioned preparation method.
[0067] The special chemical structure of the benzoxazine compounds in the present invention can be directly converted into LIG materials after laser irradiation. The highly carbon-forming benzoxazine compound structure generates local instantaneous high temperature (>2000°C) after laser irradiation, and the gasification and decomposition of the benzoxazine compounds occur almost instantly. Among them, most of the chemical bonds such as CC, CN, CO, CH in the molecular structure of benzoxazine compounds are destroyed at high temperature, and part of these elements are reorganized into graphene structures, and the other part is reorganized into gas products and released. The rapid release of gas products inhibits the accumulation of graphene sheets on the one hand, and leads to the final three-dimensional porous structural characteristics. On the other hand, a large amount of gas products also dilutes the oxygen concentration in the air, protecting the generated graphene structure from oxidation at high temperatures.
[0068] The particularity of the benzoxazine compounds in the present invention lies in their high carbon-forming molecular structure, which can be directly converted into graphene materials without polymerization into macromolecular polymers.
[0069] The benzoxazine monomer and / or its derivatives used in the present invention are fusible and soluble, allowing the graphene material to be prepared and utilized in the form of a coating or a self-supporting film. In addition, the molten (liquid) benzoxazine monomer and / or its derivatives can also be directly and evenly mixed with a dopant, which is compatible with more types of dopants and corresponding doping amounts compared to traditional precursor modification methods such as impregnation, chemical grafting, and co-curing. The method for preparing a graphene material based on a benzoxazine monomer and its derivatives provided by the present invention has a simple process, a short production cycle, and low cost. The functional form (coating, film) and composition of the prepared graphene material can be flexibly customized and regulated, which has obvious advantages over existing graphene material preparation technologies.
[0070] Another aspect of the embodiments of the present invention further provides applications of the aforementioned graphene material or graphene hybrid material and / or graphene composite material in the fields of energy storage, energy conversion, catalysis, sensing or electromagnetic shielding.
[0071] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0072] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0073] Example 1
[0074] (1) 1.0 mol of propyl gallate, 2.0 mol of furfurylamine and 5.0 mol of polyformaldehyde were reacted at 80° C. for 5 hours with dioxane as solvent to obtain a light yellow transparent solution. The unreacted raw materials were removed by washing with saturated sodium carbonate solution and water in turn. Finally, the solvent was removed by rotary evaporator to obtain a benzoxazine monomer product. Figure 1 The NMR of the obtained benzoxazine monomer is as follows: 1H NMR (400 MHz, Chloroform-d) δ7.40 (dd, J = 1.9, 0.8 Hz, 2H), 6.32 (dd, J = 3.2, 1.9 Hz, 2H), 6.24 (dd, J = 3.1, 0.8 Hz, 2H), 4.96 (s, 4H), 4.16 (t, J = 6.7 Hz, 2H), 4.13 (s, 4H), 3.89 (s, 4H), 1.68 (q, J = 7.1 Hz, 2H), 0.94 (t, J = 7.4 Hz, 3H).
[0075]
[0076] (2) The obtained benzoxazine monomer was coated on a polyethylene terephthalate (PET) film and the film was irradiated with a CO irradiation wavelength of 10.6 μm. 2 The benzoxazine monomer is irradiated by an infrared laser, and the irradiation path of the laser is programmable. Under the photothermal effect of the laser, the benzoxazine monomer is directly converted into a graphene material;
[0077] (3) Using acetone to wash away the unconverted benzoxazine monomer, a graphene material layer attached to the PET film is obtained.
[0078] Figure 2 It is a demonstration diagram of laser irradiation of benzoxazine monomer; the inventor of this case also analyzed the graphene material prepared in this embodiment. Figure 3 Digital photograph of patterned graphene material on the surface of PET film. Figure 4 The scanning electron microscope image of the graphene material shows the three-dimensional porous structure generated by the rapid release of gas products during laser irradiation. Figure 5 As shown, there are three prominent characteristic peaks: 1350cm -1 The D peaks on the left and right are disordered vibration peaks caused by sp2 carbon defects or bending. The intensity of the D peak is only related to the degree of disorder of graphene; 1580cm -1 The G peaks on the left and right are caused by the in-plane vibration of carbon atoms. The intensity ratio of the D peak to the G peak can usually be used as an important parameter to characterize the defect concentration of graphene; 2700cm -1 The 2D peak at is the second-order mode of the graphene D peak. The greater the defect concentration of graphene, the greater the intensity of the D peak and the smaller the intensity of the 2D peak. For high-quality graphene, the D peak does not exist, but the 2D peak does not disappear. Under a transmission electron microscope, see Figure 6 , the nanostructure of few-layer graphene can be observed.
[0079] Example 2
[0080] (1) 1.0 mol of catechol, 2.0 mol of aniline and 5.0 mol of polyformaldehyde were reacted at 80° C. for 5 hours with dioxane as solvent to obtain a yellow transparent solution. The unreacted raw materials were removed by washing with saturated sodium carbonate solution and water in turn. Finally, the solvent was removed by a rotary evaporator to obtain a benzoxazine monomer product;
[0081]
[0082] (2) The obtained benzoxazine monomer was coated on cotton cloth and a CO 2The benzoxazine monomer is irradiated by an infrared laser, and the irradiation path of the laser is programmable. Under the photothermal effect of the laser, the benzoxazine monomer is directly converted into a graphene material;
[0083] (3) Using acetone to wash away the unconverted benzoxazine monomer, a graphene material attached to the cotton cloth is obtained.
[0084] Figure 7 A digital photo of graphene material attached to cotton cloth.
[0085] Example 3
[0086] (1) 1.0 mol of o-phenylphenol, 1.0 mol of aniline and 3.0 mol of polyformaldehyde were reacted at 120° C. for 5 hours with xylene as solvent to obtain a yellow transparent solution. The unreacted raw materials were removed by washing with saturated sodium carbonate solution and water in turn. Finally, the solvent was removed by a rotary evaporator to obtain a benzoxazine monomer product;
[0087]
[0088] (2) coating the obtained benzoxazine monomer on glass, and irradiating the benzoxazine monomer with a laser having a wavelength of 532 nanometers, wherein the irradiation path of the laser is programmable. Under the photothermal effect of the laser, the benzoxazine monomer is directly converted into a graphene material;
[0089] (3) Using acetone to wash away the unconverted benzoxazine monomer, an independent self-supporting graphene material film is obtained.
[0090] Figure 8 This is a digital photograph of the prepared independent and self-supporting three-dimensional porous graphene film material.
[0091] Example 4
[0092] (1) 1.0 mol of pyrogallol, 2.0 mol of aniline and 5.0 mol of paraformaldehyde were reacted at 70°C for 5 hours with ethyl acetate as solvent, and then cooled to room temperature. A large amount of white powder was precipitated. It was washed with hot ethanol, filtered and dried to finally obtain a light yellow powder product;
[0093]
[0094] (2) coating the obtained benzoxazine monomer on glass, and irradiating the benzoxazine monomer with a laser having a wavelength of 450 nanometers, wherein the irradiation path of the laser is programmable. Under the photothermal effect of the laser, the benzoxazine monomer is directly converted into a graphene material;
[0095] (3) Using acetone to wash away the unconverted benzoxazine monomer, an independent self-supporting graphene material film is obtained.
[0096] Example 5
[0097] (1) 1.0 mol of pyrogallol, 2.0 mol of aniline and 5.0 mol of paraformaldehyde were reacted at 70°C for 5 hours with ethyl acetate as solvent, and then cooled to room temperature. A large amount of white powder was precipitated. The product was washed with ethanol, filtered and dried to obtain a white product.
[0098]
[0099] (2) coating the obtained benzoxazine monomer on cotton cloth, and irradiating the benzoxazine monomer with a laser having a wavelength of 800 nanometers, wherein the irradiation path of the laser is programmable. Under the photothermal effect of the laser, the benzoxazine monomer is directly converted into a graphene material;
[0100] (3) Using acetone to wash away the unconverted benzoxazine monomer, a graphene material attached to the cotton cloth is obtained.
[0101] (4) The obtained three-dimensional graphene material is made into a planar supercapacitor with a specific capacitance of 5mFcm -2 , power density is ~10mWcm -2 .
[0102] Example 6
[0103] (1) 1.0 mol of the benzoxazine monomer prepared in Example 4 was dissolved in chloroform, and 1.2 mol of triethylamine was added as an acid binding agent. 1.2 mol of nonanoyl chloride was slowly added dropwise to the above solution, and the mixture was reacted in an ice-water bath for 6 hours;
[0104] (2) The above solution after the reaction is completed is washed with 1.0 mol hydrochloric acid aqueous solution and deionized water respectively. Finally, the solvent is removed by rotation to obtain a yellow transparent nonanoyl chloride modified benzoxazine monomer;
[0105]
[0106] (3) coating the obtained benzoxazine monomer on a silicon wafer, and irradiating the benzoxazine monomer with a laser having a wavelength of 788 nanometers, wherein the irradiation path of the laser is programmable. Under the photothermal effect of the laser, the benzoxazine monomer derivative is directly converted into a graphene material;
[0107] (4) Using acetone to wash away the unconverted benzoxazine monomer, an independent self-supporting graphene material is obtained.
[0108] Example 7
[0109] (1) 1.0 mol of the benzoxazine monomer prepared in Example 5 was dissolved in chloroform, and 1.2 mol of sodium carbonate was added. 3.0 mol of bromopentane was slowly added dropwise to the above solution and reacted for 6 hours;
[0110] (2) The above solution after the reaction is completed is washed with 1.0 mol hydrochloric acid aqueous solution and deionized water respectively. Finally, the solvent is removed by rotation to obtain a yellow transparent nonanoyl chloride modified benzoxazine monomer;
[0111]
[0112] (3) coating the obtained benzoxazine monomer on a silicon wafer, and irradiating the benzoxazine monomer with a laser having a wavelength of 10.6 microns, wherein the irradiation path of the laser is programmable. Under the photothermal effect of the laser, the benzoxazine monomer derivative is directly converted into a graphene material;
[0113] (4) Using acetone to wash away the unconverted benzoxazine monomer, an independent self-supporting graphene material film is obtained.
[0114] Example 8
[0115] (1) The benzoxazine monomer derivative in Example 6 and urea were uniformly blended at a mass ratio of 10:1, and stirred at 70° C. to obtain a urea / benzoxazine monomer derivative composition;
[0116]
[0117] (2) The obtained composition was coated on a silicon wafer and a CO 2 An infrared laser is used to irradiate the urea / benzoxazine monomer derivative composition, and the composition is directly converted into a nitrogen-doped graphene hybrid material under the photothermal effect of the laser;
[0118] (3) Using acetone to wash away the unconverted benzoxazine monomer, an independent self-supporting nitrogen-doped graphene hybrid material film is obtained.
[0119] Figure 9a-9c The scanning electron microscope image, Raman spectrum data, and X-ray photoelectron spectroscopy data of the obtained nitrogen-doped graphene hybrid material are shown in Figure 1. The results of X-ray electron spectroscopy show that the N content in the N-doped graphene hybrid material is 7.8 at%.
[0120] Example 9
[0121] (1) The benzoxazine monomer derivative in Example 6 was mixed with TiO 2 The nanoparticles were uniformly blended at a mass ratio of 10:1 and stirred at 70 °C to obtain TiO2 Nanoparticle / benzoxazine monomer derivative compositions;
[0122]
[0123] (2) The obtained composition was coated on a silicon wafer, and a laser with a wavelength of 248 nanometers was used to irradiate TiO 2 The nanoparticle / benzoxazine monomer derivative composition is irradiated with laser, and the composition is directly converted into TiO under the photothermal effect of the laser. 2 Nanoparticles and TiC nanoparticles (part of TiO 2 The nanoparticles react with the carbon material at high temperature to generate a graphene composite material loaded with TiC nanoparticles;
[0124] (3) Use acetone to wash away the unconverted benzoxazine monomer to obtain an independent self-supporting TiO 2 Nanoparticles and TiC nanoparticle-loaded graphene composite films.
[0125] Fig.10 The obtained TiO 2 X-ray diffraction images of graphene materials loaded with TiC nanoparticles and TiC nanoparticles.
[0126] Example 10
[0127] (1) The benzoxazine monomer derivative in Example 6 and ferric acetylacetonate were uniformly blended in a mass ratio of 10:3, and stirred at 70° C. to obtain a ferric acetylacetonate / benzoxazine monomer derivative composition;
[0128]
[0129] (2) coating the obtained composition on a silicon wafer, and irradiating the iron acetylacetonate / benzoxazine monomer derivative composition with an infrared laser having a wavelength of 9.3 μm, whereby the composition is directly converted into a graphene composite material loaded with iron nanoparticles under the photothermal effect of the laser;
[0130] (3) Using acetone to wash away the unconverted benzoxazine monomer, an independent self-supporting iron nanoparticle-loaded graphene composite film is obtained.
[0131] (4) The prepared iron nanoparticle-loaded graphene composite material was used as an electromagnetic shielding film with an electromagnetic shielding effectiveness of 24.8 dB.
[0132] Embodiment 11
[0133] (1) The benzoxazine monomer derivative in Example 7 and zinc acetylacetonate were uniformly mixed in a mass ratio of 10:3, and stirred at 70° C. to obtain a zinc acetylacetonate / benzoxazine monomer derivative composition;
[0134]
[0135] (2) coating the obtained composition on a silicon wafer, and irradiating the zinc acetylacetonate / benzoxazine monomer derivative composition with a laser having a wavelength of 9.3 μm, whereby the composition is directly converted into a graphene composite material loaded with Zn nanoparticles and ZnO nanoparticles under the photothermal effect of the laser;
[0136] (3) Using acetone to wash away the unconverted benzoxazine monomer, an independent self-supporting Zn nanoparticle and ZnO nanoparticle-loaded graphene composite film is obtained.
[0137] Example 12
[0138] (1) The benzoxazine monomer derivative in Example 7 and the carbon fiber felt were uniformly blended in a mass ratio of 1:1, and bubbles were extracted in a vacuum oven at 90° C. for 30 min to allow the benzoxazine monomer derivative to fully penetrate the carbon fiber felt, thereby obtaining a carbon fiber felt / benzoxazine monomer derivative composition;
[0139]
[0140] (2) The carbon fiber felt / benzoxazine monomer derivative composition is exposed to laser irradiation with a wavelength of 9.3 μm. Under the photothermal effect of the laser, the composition is directly converted into a graphene / carbon fiber composite material.
[0141] (3) The unconverted benzoxazine monomers were washed away using acetone.
[0142] Comparative Example 1
[0143] (1) Take an appropriate amount of the benzoxazine monomer in Example 4 and place it in a 10*10 cm silica gel mold;
[0144] (2) sequentially placing in an oven at 180° C. and 220° C. for curing for 2 hours each to obtain a polybenzoxazine resin;
[0145] (3) The obtained resin sheet was subjected to a 10.6 μm CO 2 Infrared laser irradiation is used to convert and generate a graphene thin layer on the resin surface;
[0146] (4) Since the polymer material is insoluble, the obtained graphene material cannot be separated from the resin matrix and can only be scraped off in the form of powder, but cannot exist in the form of an independent self-supporting graphene film.
[0147] Comparative Example 2
[0148] (1) The benzoxazine monomer derivative in Example 6 and ferric acetylacetonate were uniformly blended in a mass ratio of 10:3, and stirred at 70° C. to obtain a ferric acetylacetonate / benzoxazine monomer derivative composition;
[0149] (2) placing the obtained composition in a 10*10 cm silica gel mold, and curing at 150° C. and 180° C. for two hours respectively to obtain an iron acetylacetonate / polybenzoxazine resin sheet;
[0150] (3) The obtained resin sheet was subjected to a 10.6 μm CO 2 By infrared laser irradiation, a thin layer of graphene composite material loaded with iron nanoparticles (thickness 35 μm) was obtained on the resin surface.
[0151] (4) Since polymers are insoluble, the obtained graphene composite material loaded with iron nanoparticles can only be attached to the surface of the polymer resin and cannot be used in the form of an independent self-supporting graphene film. The electromagnetic shielding effectiveness test of the resin sheet attached with the graphene composite material showed that it only had an electromagnetic shielding effectiveness of 15.2 dB.
[0152] Comparative Example 3
[0153] (1) The benzoxazine monomer derivative in Example 6 and urea were uniformly blended at a mass ratio of 10:1, and stirred at 70° C. to obtain a urea / benzoxazine monomer derivative composition;
[0154] (2) placing the obtained composition in a 10*10 cm silica gel mold, and curing at 150° C. and 180° C. for two hours respectively to obtain a urea / polybenzoxazine resin sheet;
[0155] (3) The benzoxazine monomer undergoes phase separation from urea during the crosslinking and curing process, and a large amount of urea particles precipitate from the benzoxazine resin phase.
[0156] (4) Using CO with a wavelength of 10.6 microns 2 The urea / polybenzoxazine resin sheet is irradiated by an infrared laser, and the resin sheet is directly converted into a nitrogen-doped graphene hybrid material under the photothermal effect of the laser.
[0157] (3) The nitrogen-doped graphene hybrid material was characterized using X-ray electron spectroscopy, and the results showed that the N-doping content was 4.8 at%.
[0158] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0159] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a graphene material based on benzoxazine compounds, characterized in that include: The benzoxazine compound is irradiated with a laser to convert the benzoxazine compound into a graphene material based on the benzoxazine compound; the wavelength of the laser is 10.6 μm to 248 nm; Wherein, the benzoxazine compound includes a benzoxazine monomer and / or a benzoxazine monomer derivative; and the benzoxazine compound is a liquid material.
2. The preparation method according to claim 1, characterized in that: The graphene material includes few-layer graphene.
3. The preparation method according to claim 2, characterized in that: The number of layers of the graphene material is 2 to 9.
4. The preparation method according to claim 2, characterized in that: The graphene material also includes a small amount of graphite and / or amorphous carbon.
5. The preparation method according to claim 1, characterized in that include: The mixed reaction system including a phenol source, an amine source, polyformaldehyde and / or formaldehyde is reacted at 70 to 120° C. for 4 to 8 hours to obtain the benzoxazine monomer.
6. The preparation method according to claim 5, characterized in that: The phenol source has a structure as shown in formula (I): Wherein, R1, R2, R3, and R4 are independently selected from any one of hydrogen atom, hydroxyl group, carboxyl group, nitro group, halogen group, substituted or unsubstituted alkyl group, olefin group, ester group, alkoxy group, phenyl group, and naphthyl group; The amine source has a structure as shown in formula (II): H2N-R5 Wherein, R5 is selected from substituted or unsubstituted phenyl, furfuryl or naphthyl.
7. The preparation method according to claim 1, characterized in that include: Using any one of acyl halide, alcohol or alkyl halide to react with the benzoxazine monomer to obtain the benzoxazine monomer derivative; Wherein, the acyl halide has a structure as shown in formula (III): wherein X is selected from chlorine, bromine or iodine, and R6 is selected from substituted or unsubstituted alkyl, alkoxy, phenyl or naphthyl; The alcohol or alkyl halide has a structure as shown in formula (IV): X-R7 Formula (IV) Wherein, X is selected from hydroxyl, chlorine, bromine or iodine, and R7 is selected from substituted or unsubstituted alkyl, alkoxy, phenyl or naphthyl.
8. A graphene material based on benzoxazine compounds prepared by the preparation method according to any one of claims 1 to 7.
9. A method for preparing a graphene hybrid material and / or a graphene composite material based on a benzoxazine compound, characterized in that include: Mixing a benzoxazine compound with a doping precursor to form a composition, and then irradiating the composition with a laser to obtain a graphene hybrid material and / or a graphene composite material based on the benzoxazine compound; The wavelength of the laser is 10.6 μm to 248 nm; Wherein, the benzoxazine compound includes a benzoxazine monomer and / or a benzoxazine monomer derivative; and the benzoxazine compound is a liquid material.
10. The preparation method according to claim 9, characterized in that: The doping precursor is selected from liquid and / or powder of organic and / or inorganic substances.
11. The preparation method according to claim 10, characterized in that: The doping precursor is selected from any one or a combination of two or more of metal nanoparticles, metal oxide nanoparticles, metal carbide nanoparticles, metal salts, metal organic compounds, MXene, graphene and its derivatives, carbon nanotubes, carbon fibers, carbon nanofibers, zeolites, nitrides, boric acid, boric acid esters, phosphides, sulfides, and fluorides.
12. The preparation method according to claim 9, characterized in that: The graphene hybrid material and / or graphene composite material includes few-layer graphene; the graphene hybrid material and / or graphene composite material also includes graphite and / or amorphous carbon.
13. A graphene hybrid material and / or graphene composite material based on benzoxazine compounds prepared by the preparation method according to any one of claims 9 to 12.
14. Use of the graphene material based on benzoxazine compounds according to claim 8 or the graphene hybrid material and / or graphene composite material based on benzoxazine compounds according to claim 13 in the fields of energy storage, energy conversion, catalysis, sensing or electromagnetic shielding.
Citation Information
Patent Citations
Polycondensation catalyst for polyester synthesis as well as preparation method and application of polycondensation catalyst
CN113549207A
Preparation method of polybenzoxazine resin-based graphene and product
CN110482531A
Preparation method and application of metal oxide nanoparticle loaded three-dimensional graphene material
CN113060721A